PHOSPHOROUS SEED COATING AFFECT TO GERMINATION, PHOTOSYNTHETIC PIGMENTS AND YIELD OF RAPE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Rape (Brassica napus L. var. napus) is long ago-known vegetable of Brassicaceae in agriculture. It is important and valuable oil, forage, green-fertiliser and nectar plant. The experience of last years shows that rape is suitable for growing in conditions of Latvia, but investigations about its cultivars and growing technologies are not wide enough.The phosporus-fertilizer adding in the rape plantations is of great importance for increasing of its productivity. With the aim to reduce the expenses the phosphorus treated rape seeds are made use.In our investigations the velocity of seeds germination, germinating viability, germinating vigour, green pigments” quantity in seed-lobes and seeds” corp are studied. The conclusion is drawn that phosphorus treated seeds are of elevated physiological activity and elevated quantity of chlorophyll in seed-lobes, the seed-corp is increased for 3-70%. The velocity of the seeds” germination, germinating ability and germinat ing viability is increased too.The making use of phosphorus treated seeds is of great effectiveness because it gives the possibility to prevent phosphorus-lack in plants and to increase physiological activity and productivity of plants.